O que nos diz de nós o delírio?: uma compreensão psicanalítica sobre as relações na saúde mental - Albuquerque, Mariana Pelizer de (2010)
This study was motivated by the question of the place of insanity and its relationship with the Anti-Asylum and Psychiatric Reform, according to Mental Health professionals and users of a CAPS Centro de Atenção Psicossocial (Psychosocial Care Center), an alternative to psychiatric hospitals. The research was built from the search of a place for insanity, inside and outside walls, inside and outside of us and the question: is there room for madness? Thus, I set out to investigate the relationship established in a CAPS in Uberlândia-MG, Brasil and the fundamentals it was built upon. The interpretive method for breaking fields, suggested by Herrmann, helped me find a new way of looking at and facing insanity. In this perspective, delirium goes through and is gone through by conjunctions of reality or by the producer of the meanings of relationships. I discuss delirium through the prism of Fields Theory, a movement that seeks to rescue the importance of the interpretative method from the psychoanalytic theory and technique. To accomplish this work, I used a clinical case treated in the institution and reports from professionals on their routine at the same mental health service institution. Reflecting on routine, as a mental function, proposed in the theory of Herrmann and structured routine in CAPS, I was intrigued about the meanings of routine at this particular mental health service. From there, I tried to outline some forms of relationships that are established and the basis that supported them. I tried to put myself in a typical position of the psychoanalytic method, that is, the questioner-interpretant, and this enabled me to live in other (s) place (s). A literary text emerged as an effective interpretant integrating the transit time of discovery. In evoking Alice in Wonderland by Lewis Carol, writing my apprehensions took a new configuration. A space opened up for moving the reflection of the place or places of insanity, search and repudiation by the different, of wonder and openness to possible new directions. Somehow the delirious speech of the patient seems to expose shortcomings in the organization of the service and other logical operations of the institution, and uncover the reasonings of relations and the contemporary world. These findings were put into dialogue with the Theory of Balman about the contemporary, unfolding into a broadening of understanding of the problem investigated.